Autologous Stem Cells in Achilles Tendinopathy (ASCAT): protocol for a phase IIA, single-centre, proof-of-concept study. Issue 5 (14th May 2018) - Goldberg, Andrew J; Zaidi, Razi; Brooking, Deirdre; Kim, Louise; Korda, Michelle; Masci, Lorenzo; Green, Ruth; O'Donnell, Paul; Smith, Roger
Abstract : Introduction: Achilles tendinopathy (AT) is a cause of pain and disability affecting both athletes and sedentary individuals. More than 150 000 people in the UK every year suffer from AT. While there is much preclinical work on the use of stem cells in tendon pathology, there is a scarcity of clinical data looking at the use of mesenchymal stem cells to treat tendon disease and there does not appear to be any studies of the use of autologous cultured mesenchymal stem cells (MSCs) for AT. Our hypothesis is that autologous culture expanded MSCs implanted into an area of mid-portion AT will lead to improved pain-free mechanical function. The current paper presents the protocol for a phase IIa clinical study. Methods and analysis: The presented protocol is for a non-commercial, single-arm, open-label, phase IIa proof-of-concept study. The study will recruit 10 participants and will follow them up for 6 months. Included will be patients aged 18–70 years with chronic mid-portion AT who have failed at least 6 months of non-operative management. Participants will have a bone marrow aspirate collected from the posterior iliac crest under either local or general anaesthetic. MSCs will be isolated and expanded from the bone marrow. Four to 6 weeks after the harvest, participants will undergo implantation of the culture expanded MSCs under local anaesthetic and ultrasound guidance. The primary outcome will be safety as defined by the incidence rate of serious adverse reaction. The secondary outcomes will be efficacy as measured by patient-reported outcome measures and radiological outcome using ultrasound techniques. Ethics and dissemination: The protocol has been approved by the National Research Ethics Service Committee (London, Harrow; reference 13/LO/1670). Trial findings will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: NCT02064062.